Magda y la pinata magica - Chavarria-Chairez, Becky; Vega, Anne; Ventura, Gabriela Baeza (Houston, Tex. : Pinata Books, 2001)
When Tio Manuel brings home a very special piñata for Gabriel's birthday party, his sister Magda figures out an ingenious way to preserve it and still make the party guests happy.
Accelerated Reader
Text in English and Spanish.
Keywords: Pinatas -- Juvenile fiction; Birthdays -- Juvenile fiction; Parties -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Spanish language materials -- Bilingual -- Juvenile literature; Pinatas -- Novela juvenil; Cumpleanos -- Novela juvenil; Fiestas -- Novela juvenil; Hermanos -- Novela juvenil; Materiales bilingues en espanol -- Literatura juvenil